Implementation of Integrity Thematic Learning in The New Normal Era at SD Negeri Banua Anyar 2 - Yudha Rizky Rawidafany; Syaharuddin Syaharuddin; Mutiani Mutiani (Universitas Lambung Mangkurat, 2023)
Learning is part of education; education is an essential means of improving the quality of human resources in ensuring the sustainability of a nation's Development so that the application of learning in the education system can become a benchmark for the quality of the nation's future progress. Early education in Indonesia starts from Elementary School (SD) and through the application of cooperative learning in elementary schools with the 2013 curriculum. The government emphasises using integrative thematic learning approaches in learning basic subjects in elementary schools and a scientific approach in the learning process. So that during the implementation period in elementary schools, there was an impact on the new normal era after COVID-19, especially at the Banua Anyar 2 Public Elementary School learning activities. This study used a qualitative approach to examine the subject in the planning process, applying integrative thematic learning. So this study aims to determine the application of integrative thematic learning during the new normal era in class V at SD Negeri Banua Anyar 2 Banjarmasin.